PEMANFAATAN TANAMAN LIDAH BUAYA (Aloe Vera) MENJADI NATA DE ALOE SEBAGAI MAKANAN BERSERAT PADA KELOMPOK WANITA TANI DI DESA PUCAK KABUPATEN MAROS - Maimuna Nontji; Suriyanti HS; Muliaty Galib; Anwar Robbo (Universitas Mataram, 2023)
Aloe vera is one type of plant that has many benefits, including as a food and health drink, basic ingredients of medicines and cosmetics. Aloe vera can be made nata de aloe with a simple process using materials and tools that are easily available, nata de aloe is a fruit ice mixture that is fibrous, low in calories, contains good nutrition for people with diabetes and is very suitable for consumption as a diet drink. This activity aims to increase the knowledge and skills of the Anyelir farmer group in Pucak village, in utilizing the aloe vera plant to become nata de aloe, as a fibrous health food product. This activity is carried out using counseling methods, direct practice and training as well as assistance in making nata de aloe in a simple using tools and materials that are easily available and can be carried out by all members of the community. Results: the people of Pucak Village in general are familiar with the aloe vera plant, even in every yard they have collected this plant. However, not much is known about its use. Based on observations, the general public only knows the benefits of aloe vera as a hair-fertilizing plant, nothing more than that. After this counseling, the knowledge and skills of the community increased, especially in utilizing the aloe vera plant to make nata de aloe as a fibrous food product, besides that the community could know and understand the health benefits of the aloe vera plant. Furthermore, they can produce nata de aloe to increase household income. Community knowledge and skills increase in terms of the process of making nata de aloe, which can then produce products and increase income.